Multilingualism in today’s society: growing up with two or more languages - Bordin, Sofia Xanthopoulos; Pinheiro, Luciana Santos (BELT - Brazilian English Language Teaching Journal, 2012)
The objective of this article is to present bilingualism and some of its diverse aspects and applications in the modern world. It provides definitions of how bilingualism and multilingualism are perceived by different theorists and presents some of the problems and conflicts related to the two concepts. Furthermore, it looks into the similarities and differences of first language and second language acquisition and bilingualism from birth and shows the challenges involved for both the parents and children of bilingual families. The article also presents the results of a qualitative research that was made with 11 bilinguals and its analysis based on Skutnabb- Kangas’ classification of bilinguals. It concludes that language is a key factor that defines our relationship with other individuals and that multilingualism is a worldwide phenomenon in today’s multicultural world. Key words: bilingualism, multilingualism, multicultural.